The Effectiveness of Audiovisual in Improving English Speaking Skills In Junior High School Students - Ismah Nazhifah; Yani Lubis (South Sulawesi Education Development (SSED), 2024)
This research focuses on teaching speaking skills using Audio Visual to first grade students in one of the schools in the city of Medan. This study compares the results student achievement in speaking before and after using Audio Visual teaching method. The population of this study totaling 21 students and the sample was all students in that class. From the analyzed data there was an increase in all four aspects. Based on the data, the pronunciation is which is most improved by the Audio Visual method. There was an increase of students in speaking after students are taught to use Audio Visual method. The results show that students have a positive attitude response to the use of Audio Visual because almost 90% of the responses were positive towards the use of Audio Visual methods to teach speaking. Technological developments seem to have had many positive impacts about education. Technology provides various fun learning media student. One of the technological developments that can be used as learning the medium is YouTube. YouTube provides various types of videos related to learning. In learning English, EFL learners can find various types of videos that can be helpful learning process. Therefore, YouTube can help students to improve their abilities language skills, especially speaking skills. Because of that, it is recommended that English teachers who have similar problems also do the same try using Audio Visual to teach speaking.